2014
DOI: 10.1016/j.jpaa.2013.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Lifting via cocycle deformation

Abstract: Abstract. We develop a strategy to compute all liftings of a Nichols algebra over a finite dimensional cosemisimple Hopf algebra. We produce them as cocycle deformations of the bosonization of these two. In parallel, we study the shape of any such lifting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 33 publications
0
47
0
Order By: Relevance
“…One of the main purposes of this article is to present the recipe to construct liftings in full detail; this is presented in §4 and an example is developed in §5. Although the strategy developed in [5] applies in a more general level, we restrict ourselves for pedagogical reasons to the following setting:…”
Section: The Diagonal Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main purposes of this article is to present the recipe to construct liftings in full detail; this is presented in §4 and an example is developed in §5. Although the strategy developed in [5] applies in a more general level, we restrict ourselves for pedagogical reasons to the following setting:…”
Section: The Diagonal Settingmentioning
confidence: 99%
“…Starting with G and V , the classification of finitedimensional Hopf algebras with abelian coradical has been achieved throughout the collaborative work of many authors, specially those of Andruskiewitsch and Schneider [8,10], Heckenberger [26] and Angiono [14,13]. The final step was recently completed by the authors in [16], based on a strategy to construct Hopf algebras -the liftings-developed in [5] and [4]. In this article, we shall review the development of this classification and give detailed instructions about how to carry on this program on each example.…”
Section: Introductionmentioning
confidence: 99%
“…Then the multiplication in A induces an isomorphism R⊗k G −→ A of k G -bimodules [AAGMV,Lemma 4.1]. Hence we can think of R as a left k G -submodule of A and therefore…”
Section: Representations Of Copointed Hopf Algebrasmentioning
confidence: 99%
“…Any spherical Hopf algebra H has an associated tensor category Rep(H) which is a quotient of Rep(H), see [AAGMV,BaW1,BaW2] for the background of this subject. Moreover, Rep(H) is semisimple but rarely is a fusion category in the sense of [ENO], i. e. Rep(H) rarely has a finite number of irreducibles.…”
Section: Ismentioning
confidence: 99%
“…This classification was completed by Angiono and Garcia Iglesias in [AG19], where it is also shown that all Hopf algebras whose coradical is an abelian group algebra are cocycle deformations of their associated graded Hopf algebras. For more classification results of non-semisimple Hopf algebras in which cocycle deformations appear, see [AAIMV14], [FGM19], [GarM15], [GruM] and [AV11].…”
Section: Introductionmentioning
confidence: 99%